Developmental roles of Auxin Binding Protein 1 in Arabidopsis thaliana. (February 2021) - Gelová, Zuzana; Gallei, Michelle; Pernisová, Markéta; Brunoud, Géraldine; Zhang, Xixi; Glanc, Matouš; Li, Lanxin; Michalko, Jaroslav; Pavlovičová, Zlata; Verstraeten, Inge; Han, Huibin; Hajný, Jakub; et al.
Highlights: ABP1 expression overlaps with auxin maxima but it is not regulated by auxin. ABP1 activity is not required for transcriptional auxin signaling. abp1 loss-of-function results in largely normal development in planta . ABP1 gain-of-function leads to a broad range of auxin-related developmental defects. Abstract: Auxin is a major plant growth regulator, but current models on auxin perception and signaling cannot explain the whole plethora of auxin effects, in particular those associated with rapid responses. A possible candidate for a component of additional auxin perception mechanisms is the AUXIN BINDING PROTEIN 1 (ABP1), whose function in planta remains unclear. Here we combined expression analysis with gain- and loss-of-function approaches to analyze the role of ABP1 in plant development. ABP1 shows a broad expression largely overlapping with, but not regulated by, transcriptional auxin response activity. Furthermore, ABP1 activity is not essential for the transcriptional auxin signaling. Genetic in planta analysis revealed that abp1 loss-of-function mutants show largely normal development with minor defects in bolting. On the other hand, ABP1 gain-of-function alleles show a broad range of growth and developmental defects, including root and hypocotyl growth and bending, lateral root and leaf development, bolting, as well as response to heat stress. At the cellular level, ABP1 gain-of-function leads to impaired auxin effect on PIN polar distribution and affects BFA-sensitive PIN intracellular aggregation. The gain-of-function analysis suggests a broad, but still mechanistically unclear involvement of ABP1 in plant development, possibly masked in abp1 loss-of-function mutants by a functional redundancy.